2016
DOI: 10.1021/acs.biomac.6b01136
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Copolymers Based on Glycidol and Amino Glycidyl Ether: Highly Biocompatible Polyamines Sheathed in Polyglycerols

Abstract: Functional hyperbranched polyglycerols (PGs) have recently garnered considerable interest due to their potential in biomedical applications. Here, we present a one-pot synthesis of hyperbranched PGs possessing amine functionality using a novel amino glycidyl ether monomer. A Boc-protected butanolamine glycidyl ether (BBAG) monomer was designed and polymerized with glycidol (G) through anionic ring-opening multibranching polymerization to yield a series of hyperbranched P(G-co-BBAG) with controlled molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Inspired by the advent of click chemistry, the azide functionality is regarded as a good candidate for the post-polymerization modification of polyethers due to its potential to undergo further modification by Cu-catalyzed azide–alkyne cycloaddition (CuAAC) or Staudinger reduction. As a part of our ongoing effort in the development of novel functional glycidyl ether monomer library, herein, we introduce a series of new azide-functional glycidyl ether monomers, azidoethyl glycidyl ether (AEGE), azidobutyl glycidyl ether (ABGE), and azidohexyl glycidyl ether (AHGE) that can be polymerizable under organic superbase-catalyzed AROP conditions. The homopolymerization of each monomer was compared using in situ 1 H NMR kinetic study.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the advent of click chemistry, the azide functionality is regarded as a good candidate for the post-polymerization modification of polyethers due to its potential to undergo further modification by Cu-catalyzed azide–alkyne cycloaddition (CuAAC) or Staudinger reduction. As a part of our ongoing effort in the development of novel functional glycidyl ether monomer library, herein, we introduce a series of new azide-functional glycidyl ether monomers, azidoethyl glycidyl ether (AEGE), azidobutyl glycidyl ether (ABGE), and azidohexyl glycidyl ether (AHGE) that can be polymerizable under organic superbase-catalyzed AROP conditions. The homopolymerization of each monomer was compared using in situ 1 H NMR kinetic study.…”
Section: Introductionmentioning
confidence: 99%
“…Glycidol, one of the most versatile derivatives of renewable glycerol, has been widely used as a raw material in the chemical synthesis of polyglycerols, glycidyl ethers, and polyurethanes, as well as in perfumes, cosmetics, surface coatings, detergents, and paints. In particular, since glycidol is converted to the glycerol branching unit after anionic/cationic ring-opening polymerization, a number of studies have demonstrated the availability of glycidol to produce highly branched polymers via copolymerization with other monomers. From this perspective, we hypothesized that glycidol would be a suitable branching monomer for PCL, if it can be ring-opened under the typical conditions used for synthesizing PCL, i.e., a one-pot, solvent-free, and Sn­(Oct) 2 -catalyzed polymerization. However, to date, there have been only a few reports describing the ring-opening of glycidol in the presence of Sn­(Oct) 2 . , Furthermore, to the best of our knowledge, there are no reports on the ring-opening multibranching copolymerization of CL with glycidol.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few epoxide monomers functionalized with protected amino groups reported to be polymerized by AROP: N,Ndibenzylglycidylamine (DBGA), 12,13 N,Ndiallyglycidylamine (DAGA), 14 Boc-protected butanolamine glycidyl ether (BBAG). 15 Moreover, glycidyl phthalimide is an interesting protected-amine-containing monomer which has been used to functionalize hyperbranched polyglycerols with amine groups. 16,17 However, ABSTRACT : Anionic ring-opening polymerization of glycidyl phthalimide, initiated with alcoholphosphazene base systems and based on monomer activation with a Lewis acid (iBu3Al), has been studied.…”
Section: Introductionmentioning
confidence: 99%